2015
DOI: 10.3402/jchimp.v5.28982
|View full text |Cite
|
Sign up to set email alerts
|

Partially reversible bortezomib-induced cardiotoxicity: an unusual cause of acute cardiomyopathy

Abstract: Chemotherapy-associated cardiotoxicity can present as a spectrum from arrhythmia to acute congestive heart failure. Unlike anthracyclines, proteasome inhibitors – for example, bortezomib – are not notorious for causing cardiotoxicity in absence of pre-existing cardiac dysfunction or without concomitant use of other cardiotoxic agents. We describe a 66-year-old woman with end-stage renal disease who developed acute dyspnea hours after a third treatment with bortezomib for IgG kappa myeloma. The Naranjo adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 12 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…One meta-analysis of the 5718 subjects demonstrated that there was no increased risk of cardiotoxicity, 61 whereas reports suggest otherwise. 62,63 As carfilzomib forms irreversible interactions, its risk of cardiomyopathy is higher. In the landmark ASPIRE trial, 3.8% of the patients developed cardiomyopathy compared with 1.8% in the control group, as well as higher rate of uncontrolled hypertension in the carfilzomib group (4.3%) vs controls (1.8%).…”
Section: Chemotherapy Agents Associated With Ctrcdmentioning
confidence: 99%
“…One meta-analysis of the 5718 subjects demonstrated that there was no increased risk of cardiotoxicity, 61 whereas reports suggest otherwise. 62,63 As carfilzomib forms irreversible interactions, its risk of cardiomyopathy is higher. In the landmark ASPIRE trial, 3.8% of the patients developed cardiomyopathy compared with 1.8% in the control group, as well as higher rate of uncontrolled hypertension in the carfilzomib group (4.3%) vs controls (1.8%).…”
Section: Chemotherapy Agents Associated With Ctrcdmentioning
confidence: 99%
“…This partly depends on whether the drug is used in patients with significant cardiovascular disease risk factors and on previous exposure to known cardiotoxic chemotherapeutic agents such as anthracyclines, making it difficult to determine if a single or a combination of factors cause the cardiac events [108,109]. However, since bortezomib has been approved to be used in the clinical setting, many reports have been published addressing its cardiovascular toxicity [110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126]. The cardiovascular adverse events so far associated with bortezomib treatment include heart failure, that is the most frequently reported cardiac side effect [110][111][112][113][114][115][116][117][118][119][120], conduction disorders such as complete atrioventricular block [110,[121][122][123], arrhythmias including atrial fibrillation [110,124], ischemic heart disease [125], pericardial effusion [112,126] and orthostatic hypotension [27,115].…”
Section: Cardiovascular Toxicity: the Low Rate And Reversible Side Efmentioning
confidence: 99%
“…13 Therefore, possible cardiotoxicity and a decrease in cardiac function secondary to bortezomib therapy cannot be explained simply by the interference of cellular growth, mitosis, or both. Cardiotoxicity from bortezomib has been reported to cause decreases in systolic function with reduced ejection fraction and subsequent heart failure, [3][4][5]14,15 as well as cardiac conduction disturbances 16 and accelerated atherosclerotic disease. 17 Carfilzomib and ixazomib have also caused cardiotoxity, so this may represent a drug class effect.…”
Section: A B Cmentioning
confidence: 99%